Stereotactic Body Radiation Therapy for Oligometastatic Breast Cancer: A Retrospective Multicenter Study - Lemoine, Pauline; Bruand, Marie; Kammerer, Emmanuel; Bogart, Emilie; Comte, Pauline; Royer, Philippe; Thariat, Juliette; Pasquier, David (Frontiers in Oncology, 2021)
Introduction Stereotactic radiotherapy may improve the prognosis of oligometastatic patients. In the literature, there is very little data available that is specific to breast cancer. Materials and Methods We conducted a multicenter retrospective study. The primary objective was to estimate progression-free survival after stereotactic body radiotherapy (SBRT) using Cyberknife of breast cancer oligometastases. The secondary objectives were to estimate overall survival, local control, and toxicity. The inclusion criteria were oligometastatic breast cancer with a maximum of five lesions distributed in one to three different organs, diagnosed on PET/CT and/or MRI, excluding brain metastases and oligoprogressions. This was combined with systemic medical treatment. Findings Forty-four patients were enrolled from 2007 to 2017, at three high-volume cancer centers. The patients mostly had one to two lesion(s) whose most widely represented site was bone (24 lesions or 44.4%), particularly in the spine, followed by liver (22 lesions or 40.7%), then pulmonary lesions (six lesions or 11.1%). The primary tumor expressed estrogen receptors in 33 patients (84.6%); the status was HER2+++ in 7 patients (17.9%). The median dose was 40 Gy (min-max: 15-54) prescribed at 80% isodose, the median number of sessions was three (min-max: 3-10). The median D50% was 42 Gy (min max 17-59). After a median follow-up of 3.4 years, progression-free survival (PFS) at one year, two years, and three years was 81% (95% CI: 66-90%), 58% (95% CI: 41-72%), and 45% (95% CI: 28-60%), respectively. The median PFS was 2.6 years (95% CI: 1.3 – 4.9). Overall survival at three years was 81% (95% CI: 63-90%). The local control rate at two and three years was 100%. Three patients (7.3%) experienced G2 acute toxicity, no grade ≥3 toxicity was reported. Conclusion The PFS of oligometastatic breast cancer patients treated with SBRT appears long, with low toxicity. Local control is high. SBRT for oligometastases is rarely applied in breast cancer in light of the population in our study. Phase III studies are ongoing.